Dual Mode Design On Backend Development Of Django-Based Kegiatan Belajar Mengajar (KBM) Application - Raden D Ahmad H; Davit Hermawan; Endra Abdul Hadi; Nurdiansyah Permana; Dani Rohpandi (Journal of Multimedia Technology and Applied Software, 2025)
Educators often face significant administrative burdens from tasks like lesson planning and reporting, which impede efficiency and reduce direct student interaction time. This research aimed to design and develop a backend architecture for a learning activity management (KBM) application featuring a novel dual-mode system to serve both independent teachers and formal institutions. Employing an Agile methodology and the Django framework, the study developed a robust backend with a comprehensive database, models, views, and URL configurations. White-box testing was conducted to validate the internal logic. The findings confirm the successful implementation of a dual-mode architecture using Role-Based Access Control (RBAC), which effectively segregates data and permissions according to user roles. The developed prototype demonstrates a scalable and secure foundation for the application. The primary implication of this research is a validated architectural model for multi-tenancy educational software, offering a practical solution to streamline administrative workflows and enhance educator productivity. Future work should focus on frontend development and user acceptance testing.